Chemicals isolated from Justicia adhatoda Linn reduce fitness of the mosquito, Aedes aegypti L. Issue 4 (7th March 2017) - Thanigaivel, Annamalai; Senthil‐Nathan, Sengottayan; Vasantha‐Srinivasan, Prabhakaran; Edwin, Edward‐Sam; Ponsankar, Athirstam; Selin‐Rani, Selvaraj; Pradeepa, Venkatraman; Chellappandian, Muthiah; Kalaivani, Kandaswamy; Abdel‐Megeed, Ahmed; Narayanan, Raman; Murugan, Kadarkarai
Abstract: Extracts from Justicia adhatoda L. (Acanthaceae) strongly reduced the fitness of the mosquito, Aedes aegypti Linn. The methanolic extracts inhibited several enzymes responsible for protecting insects from oxidative and other damage, including glutathione‐S‐transferase, superoxide dismutase, cytochrome P450, and α‐ and β‐esterases. They increased repellency (maximum repellency at 100 ppm) in host‐seeking adult females using the "arm‐in cage assay." Histopathological examination showed the extracts led to serious midgut cell damage. Justicia adhatoda extracts led to reduced fecundity and oviposition of gravid females compared to controls. The extracts led to substantially reduced A. aegypti survival. We infer that the extracts have potential to reduce pathogen transmission by suppressing population growth of A. aegypti, and possibly other mosquito species.